Gold-catalyzed alkylation of silyl enol ethers with ortho-alkynylbenzoic acid esters - Aikawa, Haruo; Kaneko, Tetsuro; Asao, Naoki; Yamamoto, Yoshinori (Beilstein Journal of Organic Chemistry, 2011)
Unprecedented alkylation of silyl enol ethers has been developed by the use of ortho-alkynylbenzoic acid alkyl esters as alkylating agents in the presence of a gold catalyst. The reaction probably proceeds through the gold-induced in situ construction of leaving groups and subsequent nucleophilic attack on the silyl enol ethers. The generated leaving compound abstracts a proton to regenerate the silyl enol ether structure.
Keywords: alkylation; gold catalysis; leaving group; silyl enol ether; substitution reaction